2020
DOI: 10.3390/brainsci10040197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aneurysm Patency and Mural Inflammation in an Arterial Rabbit Sidewall and Bifurcation Aneurysm Model under Consideration of Different Wall Conditions

Abstract: Background: Biological processes that lead to aneurysm formation, growth and rupture are insufficiently understood. Vessel wall inflammation and degeneration are suggested to be the driving factors. In this study, we aimed to investigate the natural course of vital (non-decellularized) and decellularized aneurysms in a rabbit sidewall and bifurcation model. Methods: Arterial pouches were sutured end-to-side on the carotid artery of New Zealand White rabbits (vital [n = 6] or decellularized [n = 6]), and into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Inflammation was observed only at 2 weeks after elastase incubation. The use of decellularization in surgical graft aneurysms has been recently reported in rabbits, 7 with similar finding of increased inflammation in the decellularized aneurysms. However, unlike the surgical model, this endovascular model does not involve vascular response to suturing at the neck.…”
Section: Basic Sciencesupporting
confidence: 57%
See 1 more Smart Citation
“…Inflammation was observed only at 2 weeks after elastase incubation. The use of decellularization in surgical graft aneurysms has been recently reported in rabbits, 7 with similar finding of increased inflammation in the decellularized aneurysms. However, unlike the surgical model, this endovascular model does not involve vascular response to suturing at the neck.…”
Section: Basic Sciencesupporting
confidence: 57%
“…However, a short time after aneurysm creation, 3 these models develop into stable aneurysms that do not demonstrate characteristics of vulnerable aneurysms in humans-namely, inflammation, intramural hemorrhage, and ultimately, rupture (reviewed in Tulamo et al 4 ), showing only some areas of thin, acellular aneurysm wall. 5 To deal with these model limitations, an innovative strategy has been developed to implant decellularized arterial grafts in rodents 6 and rabbits, 7 the former model showing both growth and rupture of these aneurysms. The objective of our study is to explore the feasibility of inducing in situ decellularization in a common rabbit model of saccular aneurysms 8 to recapitulate pathological features of unstable aneurysms and to perform comparative longitudinal non-invasive MRI of the inflammation marker myeloperoxidase (MPO).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a sidewall rabbit model, all aneurysms thrombosed spontaneously. 19 In our bifurcation series, in the ASA arm all aneurysms had partial thrombosis whereas the group without ASA had complete thrombosis in half of the aneurysms and partial thrombosis in the other half. Graft decellularization by SDS, including endothelial cells, may have contributed substantially to this high rate of thrombosis.…”
Section: Decellularized Aneurysmsmentioning
confidence: 57%
“…The call for papers on this topic was met with a great response by researchers and clinicians from all over the world. Among 16 basic science and clinical research submissions, our editorial team selected nine articles for publication after extensive peer review, which included three original papers [ 1 , 2 , 3 ], three reviews [ 4 , 5 , 6 ], two case reports [ 7 , 8 ] and one technical note [ 9 ]. The remaining seven papers were not included, thus yielding a 44% rejection rate.…”
mentioning
confidence: 99%
“…In an original study using an extracranial aneurysm model in rabbits, researchers confirmed that, under flow conditions in a bifurcation aneurysm, the organization of an intraluminal thrombus was strongly dependent on the condition of the aneurysm wall [ 2 ]. In another original work featuring an intracranial aneurysm model on rats, authors investigated how sex hormones influence the inflammatory reactions in the aneurysm walls and affect the endothelial cells of the vascular walls [ 3 ].…”
mentioning
confidence: 99%